The causal effect of family income on child health: A re-examination using an instrumental variables approach - Daniel Kuehnle (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2013)
Despite a recent growth in studies examining the association between family income and child health, very few studies investigate whether this is a causal relationship. This paper addresses this major methodological gap and examines the causal effect of family income on child health in the UK. Using rich observational data from a British cohort study, we exploit exogenous variation in local labour market characteristics to instrument for family income. We estimate the effect of family income on subjective child health and control for potential transmission channels through which income could affect child health. The results from our models provide novel evidence that income has a small but significant causal effect on subjective child health. Moreover, the analysis shows that parental health does not drive a spurious relationship between family income and child health as argued in recent contributions. We do not find significant effects of family income on chronic indicators of child health. The results are robust to different sets of instrumental variables, and to alternative measures of income.
Keywords: I1; 330; child health; income gradient; instrumental variables; transmission channels; UK